Penerapan Media Taman Satwa Untuk Meningkatkan Hasil Belajar Siswa dalam Pembelajaran IPA Kelas V di MI NU Mawaqi’ul Ulum - Hanik, Elya Umi; Roufatunnur, Roufatunnur; Machaasinaty, Tsamara; Rahmawati, Suci (Lembaga Yasin AlSys, 2021)
This study aims to improve the learning outcomes of fifth grade students at MI NU Mawaqi'ul Ulum in the first semester of the 2021/2022 academic year in the subject of Science Theme 5 Sub-theme 1 (KD 3.5), using animal park media. The subjects of this study were students of class V MI NU Mawaqi'ul Ulum which consisted of 26 students, 10 male students and 16 female students. This type of research is Classroom Action Research (CAR), where the teacher is the implementer of learning while the researcher is the observer. The data collection technique used a test technique and carried out 2 cycles. The procedures applied in each cycle include the stages of planning, implementation, observation, and reflection. The object of research is student learning outcomes. Data were analyzed descriptively and presented in tabular form. The results showed an increase in student learning outcomes, namely in the pre-cycle by 38.46%, in the first cycle increased to 80.77%, and in the second cycle 100%. So, it can be concluded that the use of the media